HOUSEHOLD WORKSHOP AS A MEDIA CORNER TO SHARE HOUSEHOLD PROBLEMS AND EFFORTS TO REDUCE DIVORCE RATE IN DISTRICT BANYUWANGI - Ansari Ansari; Mufidah Ch; Erfaniah Zuhriah (International Conference on Humanity Education and Society (ICHES), 2023)
The Sakinah Workshop Program is an innovation program from the Banyuwangi Regency TP-PKK which is a corner service for the community by providing motivation, understanding, and prevention. The main purpose of the establishment of the Sakinah Workshop program is to reduce the divorce rate in Banyuwangi Regency. This research uses an empirical-normative type of research and uses a qualitative approach. The results showed that the Sakinah Workshop in Banyuwangi Regency has not achieved the main goal, namely to reduce the divorce rate in Banyuwangi Regency, and the divorce rate in Banyuwangi Regency cannot be a benchmark for the success of Sakinah Workshop because the scope of Sakinah Workshop is not only to prevent problems for couples who are about to divorce, but more broadly, namely regarding health, safety, and also assistance to the duafa community. The efforts made by Sakinah Workshop to reduce the divorce rate are by opening a space to vent to families who are experiencing problems such as the economy, infidelity, and domestic violence.